Molecular Determinants of Calcitriol Signaling and Sensitivity in Glioma Stem-like Cells - Rehbein, Sarah; Possmayer, Anna-Lena; Bozkurt, Süleyman; Lotsch, Catharina; Gerstmeier, Julia; Burger, Michael; Momma, Stefan; Maletzki, Claudia; Classen, Carl Friedrich; Freiman, Thomas Michael; Dubinski, Daniel; Lamszus, Katrin; et al. (Cancers, 2023)
Glioblastoma is the most common primary brain cancer in adults and represents one of the worst cancer diagnoses for patients. Suffering from a poor prognosis and limited treatment options, tumor recurrences are virtually inevitable. Additionally, treatment resistance is very common for this disease and worsens the prognosis. These and other factors are hypothesized to be largely due to the fact that glioblastoma cells are known to be able to obtain stem-like traits, thereby driving these phenotypes. Recently, we have shown that the in vitro and ex vivo treatment of glioblastoma stem-like cells with the hormonally active form of vitamin D3, calcitriol (1α,25(OH)2-vitamin D3) can block stemness in a subset of cell lines and reduce tumor growth. Here, we expanded our cell panel to over 40 different cultures and can show that, while half of the tested cell lines are sensitive, a quarter can be classified as high responders. Using genetic and proteomic analysis, we further determined that treatment success can be partially explained by specific polymorphism of the vitamin D3 receptor and that high responders display a proteome suggestive of blockade of stemness, as well as migratory potential.